Pengaruh Rantai Pasok Halal Terhadap Kinerja Produksi Makanan UMKM - Irma Fahriani (UPT Penerbitan Universitas Jember, 2024)
The supply chain is a series of overall processes starting from the management, movement, storage and handling of raw materials, inventory of semi-finished goods, which ends with satisfied customers. Researchers use the R-A theory (Resource-Advantage Theory) to explain internal factors and the role of company performance. Researchers use quantitative research with survey methods with data collection techniques, namely questionnaires. The level of potential for the development of MSMEs in Jember Regency is large and continues to increase based on data from the Central Statistics Agency (BPS) Jember Regency also has the largest number of MSMEs in East Java with a total of 647,416. In addition, the market coverage it has is already extensive to various cities and provinces. This is supported by data obtained from media such as Jember radar, detik.com, Tv One, and Kompas Tv. Seeing from these data, its distribution and marketing in Mayang District are areas with the highest production compared to other areas. The population in this study were all Mayang Peanut Cake MSMEs as many as 31 Mayang Peanut Cake MSME business actors in Jember Regency. The results of this study used multiple linear regression analysis by conducting a t-test (partial) and f-test (simultaneous). The results of the analysis indicate that partially the three variables in this study, namely the halal supply chain, HR quality, marketing have a positive and significant influence on production performance. Simultaneously, the three independent variables in this study have a positive and significant influence on the performance of MSME food production.